Metodologi research - Sutrisno Hadi (Yayasan Penerbitan Fak. Psikologi UGM, 1978)
ir, jil.1,c.1 jil.2 =c.1/tr, jil.4=c.1/oen, Jil.3=c.1/wk, jl.3 c.2/ir, jil.3,c.3/tr, jil.2=c.2/en, jil.4=c.2/en, jil.3=c.4/en, jil.4=c.3/en, jil.1=c.2/ast jil.2=c.3-4/stoc2, jil.1=c.1-3, jil.2 = c.1-6 ; jil.3 =c.1-4 ; jil.4=c.1-5